Intra-procedural Transvaginal Sonography to Decrease Retained Products of Conception [35A]. (May 2020) - Larish, Alyssa; Breitkopf, Daniel C.; Hopkins, Matthew; Green, Isabel; Burnett, Tatnai; Laughlin-Tommaso, Shannon
Abstract : INTRODUCTION: Retained products of conception (POC) following uterine evacuation can lead to adverse sequelae, including hemorrhage, endometritis, intrauterine adhesions, and reoperation. Incidence of retained POC range from 1.5–3.7%. Use of procedural transvaginal sonography (TVUS) in the operating room has been proposed to help decrease this. METHODS: A retrospective review of first trimester uterine evacuation procedures from 1/2015–2/2017 was performed, noting use of transabdominal ultrasonography (TAUS), retained products of conception (sonographic findings requiring surgical or medical intervention), and complications. A practice change was implemented in May 2018, in which intra-procedural TVUS was routinely performed. A second retrospective chart review was conducted to assess for post-implementation incidence of retained POC, reoperation, and associated complications. Fisher's exact test was performed. RESULTS: Prior to implementation, 130 eligible procedures were performed during the specified timeframe, with 9/130 (6.9%) incidence of retained products of conception. TAUS was performed in 59/130 (45.4%) of procedures, and 4/9 (44.4%) of those with retained products. There were eight re-operative procedures in seven patients, and two patients were treated with misoprostol. Complications included hemorrhage, Asherman's and endometritis. Following implementation, 94 first trimester procedures were performed with transvaginal sonography, with 0 (0%) cases of retained POC ( P =.01), no incidences of re-operation ( P =.02), and one case of Asherman's. TVUS led to additional focused curettage in 20/94 (21.3%) of procedures. The endometrium was measured in 64 procedures, with a mean thickness of 5.5 mm (1–12 mm). CONCLUSION: Implementation of routine TVUS during uterine evacuation appears to reduce the incidence of retained POC and associated reoperation rates.